Baseline and on-treatment serum potassium and mortality in high risk patients: the Systolic Blood Pressure Intervention Trial (SPRINT). (25th November 2020) - Byrne, C; Pareek, M; Biering-Soerensen, T; Vaduganathan, M; Krogager, M.L; Kragholm, K.H; McCullough, M; Desai, N.R; Olsen, M.H; Bhatt, D.L
Abstract: Background: Observational studies in patients with hypertension have indicated a U-shaped association between on-treatment serum potassium levels and short-time mortality. However, the association between long-time mortality and serum potassium, and the potential modification of this association by intensive blood pressure lowering, are yet to be explored. Purpose: To assess the relationship between serum potassium levels, treatment response to intensive blood pressure lowering, and mortality. Methods: SPRINT was a randomized, controlled trial in which 9, 361 individuals ≥50 years of age, at high cardiovascular (CV) risk, but without diabetes, who had an systolic blood pressure (SBP) 130–180 mmHg, were randomized to intensive (target SBP <120mmHg) or standard antihypertensive treatment (target SBP <140mmHg). Patients with an estimated glomerular filtration rate (eGFR) <25 ml/min/1.73 m 2 or end-stage renal disease were excluded. Serum chemistry was drawn at baseline, prespecified intervals, and at close out. On-treatment serum potassium was defined as the last measurement for each participant. We examined the prognostic implications (for death from CV causes and death from any cause) of baseline and on-treatment serum potassium, using restricted cubic splines, unadjusted and adjusted for demographic, clinical, and laboratory variables. We further explored the effects of intensive blood pressure lowering across the serum potassium spectrum using interaction analyses. Results: A total of 9, 336 individuals had a serum potassium measurement available at baseline and 9, 233 individuals had at least one subsequent measurement. Mean serum potassium was similar between the two study groups (intensive 4.21 mmol/l vs. standard 4.20 mmol/l; P=0.74); however, on-treatment serum potassium was significantly lower in the intensive group (intensive 4.17 mmol/l vs. standard 4.20 mmol/l; P=0.001). Median follow-up was 3.3 years (range 0–4.8), with 365 deaths from any cause (3.9%) and 102 deaths from CV causes (1.1%) recorded during the study period. Baseline serum potassium appeared to be linearly associated with both types of mortality events (test for overall trend, P<0.05; test for non-linearity versus linearity, P>0.05) on unadjusted analysis. On-treatment serum potassium displayed a U-shaped curve with death from any cause (test for overall trend, P=0.004; test for non-linearity versus linearity, P=0.006), but was not significantly associated with death from CV causes (P>0.05) (Figure). Associations were completely lost upon multivariable adjustment (P>0.05). This was particularly due to adjustment for eGFR. The efficacy of intensive blood pressure lowering was not modified by baseline or on-treatment serum potassium (P>0.05). Conclusions: Neither baseline nor on-treatment serum potassium levels were associated with death after multivariable adjustment, including renal function. The efficacy of intensive blood pressure lowering was not modified by serum potassium. Funding Acknowledgement: Type of funding source: None